2016
DOI: 10.1371/journal.pbio.1002458
|View full text |Cite|
|
Sign up to set email alerts
|

Tracking Career Outcomes for Postdoctoral Scholars: A Call to Action

Abstract: The oversupply of postdoctoral scholars relative to available faculty positions has led to calls for better assessment of career outcomes. Here, we report the results of a study of postdoctoral outcomes at the University of California, San Francisco, and suggest that institutions have an obligation to determine where their postdoc alumni are employed and to share this information with current and future trainees. Further, we contend that local efforts will be more meaningful than a national survey, because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 6 publications
4
37
1
Order By: Relevance
“…Recent broad-scale efforts by the NIH Biomedical Workforce (BWF) Working Group (https://acd.od.nih.gov/documents/reports/Biomedical_research_wgreport.pdf) among others 5–7 are galvanizing individuals to collect and disseminate data at the institution-level 8 . Answering these calls, University of California, San Francisco researchers released a seminal study on the postdoctoral career outcomes at their institution 9 , contending that tracking career outcomes at the program level is more meaningful than national surveys, which collate information from individuals in a variety of fields and programs. This study came with limitations, however, given that the researchers only examined those within T32 program laboratories (NIH Institutional Training Grant Program for which career outcome data is more readily obtained from grant reports); and given that this study did not identify finely tuned information regarding job specifics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent broad-scale efforts by the NIH Biomedical Workforce (BWF) Working Group (https://acd.od.nih.gov/documents/reports/Biomedical_research_wgreport.pdf) among others 5–7 are galvanizing individuals to collect and disseminate data at the institution-level 8 . Answering these calls, University of California, San Francisco researchers released a seminal study on the postdoctoral career outcomes at their institution 9 , contending that tracking career outcomes at the program level is more meaningful than national surveys, which collate information from individuals in a variety of fields and programs. This study came with limitations, however, given that the researchers only examined those within T32 program laboratories (NIH Institutional Training Grant Program for which career outcome data is more readily obtained from grant reports); and given that this study did not identify finely tuned information regarding job specifics.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes data collection and curation described (Silva et al, 2016). Since this publication, we have accrued new best practices.…”
Section: Setting Up a Repositorymentioning
confidence: 99%
“…and lack of an 'adjunct' preface to their faculty title, resulting in the coding of nearly all faculty positions as "Faculty: Tenure track." Other coders concluded that a tenure-track assignment could not be made without direct confirmation from the individual, given that many institutions appoint non-tenure track assistant professors, or have eliminated the traditional tenure structure altogether [19]. This non-standardized interpretation of the categories resulted in significant discordance in the classification of faculty records.…”
Section: Tier 3: Job Functionmentioning
confidence: 99%